Dental implants: a potential cause of bone marrow edema in the jaw-preliminary report - Hirotaka Muraoka; Naohisa Hirahara; Kotaro Ito; Takumi Kondo; Shungo Ichiki; Takashi Kaneda (SpringerOpen, 2021)
Abstract Background Different magnetic resonance imaging (MRI) sequences are frequently used to examine bone marrow in the jaw, including short tau inversion recovery (STIR). MRI is a sensitive method for detecting bone marrow lesions. Currently, pantomography and computed tomography (CT) are used frequently for preoperative dental implant treatment. However, no study has evaluated bone marrow edema around dental implants using MRI. This study aimed to assess bone marrow edema in the jaw around dental implants using brain magnetic resonance images. Methods This retrospective cohort study was approved by our university ethics committee (EC19-011). A total of 17 patients (170 sites) who underwent brain MRI between April 2010 and March 2016 were analyzed. All subjects underwent scanning more than 3 years after implant placement. This study investigated two bone marrow signals (with implant site and without implant site). These two groups were then compared using Fisher's exact test. The Mann-Whitney U test was used to analyze bone marrow signal intensity as the dependent variable and the long and short-axis diameters of the implant as the independent variables. Results The were 22/31 sites (71%) and 38/139 sites (27%) of bone marrow edema in the dental implants and without dental implants groups, respectively (p < 0.001). Furthermore, there was a significant correlation between bone marrow signal intensity and the short-axis diameter of the implant (p < 0.001). Conclusion The signal intensity in the bone marrow sites in the jaw with dental implants was significantly higher than that in the sites without dental implants. The present study findings suggest that dental implants are a potential cause of bone marrow edema in the jaw.